PTU-035 Single Centre Experience With Endoclot Powder Spray For Upper Gastrointestinal Bleed. (9th June 2014) - Kasimanickam, M; Vinnamala, S; Andrew, MR; Lim, C; Ahmed, M
Abstract : Introduction: Endoclot' (EPI) and 'Hemospray' (Wilson Cook) are haemostatic powders marketed for endoscopic use. The powders desiccate bleeding lesions and promote clotting. They can be used either as an adjunct to conventional haemostatic modalities or as monotherapy. Aim: We report our early experience with Endoclot usage in upper gastrointestinal bleed. Methods: N=12 patients; M7:F5; Median age 75y (63y–92y). All were frail with multiple co-morbidities (Table 1 ). Endoscopic diagnosis: duodenal ulcer (6), bleeding GI lymphoma (2), gastric ulcer (1), post gastric polyp biopsy bleed (1), GIST (1) and Mallow Weiss tear (1). Endoclot was used as monotherapy in 3/12 and as adjunct in 9/12. All patients had immediate haemostasis and one patient had late re bleed at 120hrs (8%). 1/12 died within 24hr. 6/12 were alive at 30 days. Results: Conclusion: Haemostatic powder spray is a promising new technique, particularly for difficult bleeds in frail patients. Reference: Leahy A, et al ., Early clinical experience of endoclot™ in the treatment of acute gastro-intestinal bleeding. Gut 2013;62:A149 Disclosure of Interest: None Declared.